The Relationship between Critical Thinking and Information Literacy among Students of the School of Management and Medical Information Sciences of Tehran University of Medical Sciences Iran - Zahra Azami; Hamid Salehiniya (Kerman University of Medical Sciences, 2016)
Background & Objective: Information literacy is a critical requirement for access to information in the communication age in the community Through using critical thinking skills valid and reliable information can be obtained This research was conducted to determine the relationship of critical thinking with information literacy among student of the School of Management and Medical Information Sciences of Tehran University of Medical Sciences Iran Methods: This analytical crosssectional study was conducted on 338 students of the School of Management and Medical Information Sciences of Tehran University of Medical Sciences in 2014 The valid and reliable California Critical Thinking Skills TestForm B (CCTST) and the Information Literacy Standard Questionnaire were used for collecting data The collected data were analyzed using descriptive statistics and correlation coefficient test in SPSS software Results: The critical thinking skills among students were at a low level A weak relationship was observed between the mean score of critical thinking and information literacy (P = 0050) In addition students information literacy had a positive correlation with inference components (r = 012 P = 0040) and analysis components of critical thinking (r = 16 P = 0006) Conclusion: Given the low level of critical thinking in students and the relationship between the components of critical thinking and information literacy the implementation of programs to improve students critical thinking is recommended This is necessary due to the dependence of the increase in students information literacy on critical thinking